(untitled) (Bangladesh Critical Care Journal, 2016)
Central nervous system (CNS) tuberculous meningitis is a progressive disease that presents in many ways. CNS TB is encountered frequently in areas of high prevalence of tuberculosis and dissemination is common. An 18 year old female presented with complaints of headache, low grade fever & double vision. We found cranial nerve palsy & focal neurological signs during examination. Work up revealed cerebral spinal fluid (CSF) study consistent with acute lymphocytic meningitis. Magnetic resonance imaging (MRI) revealed multiple tuberculomas with gadolinium enhancement & cerebral infarction on basal ganglia. Given the characteristic CSF and MRI finding for Tuberculosis (TB), positive MT & choroidal tubercle on fundoscopy, ischemic stroke due to tubercular meningitis is made. The patient showed significant improvement after anti tuberculosis therapy was begun. CNS TB is a treatable disease but can be fatal if not detected or treated. Clinicians should be aware of key clinical features of TB meningitis, and maintain a high level of suspicion when patients present with focal neurological signs. Bangladesh Crit Care J September 2016; 4 (2): 128-130